2001
DOI: 10.1007/s001340100942
|View full text |Cite
|
Sign up to set email alerts
|

Determination of plasma volume by indocyanine green – validation of the method and use in patients after cardiopulmonary bypass

Abstract: PV determination by peripheral i. v. injection of ICG produced reliable and consistent results when a reactive hyperaemia was produced by a tourniquet prior to injection. Therefore, central venous injection of ICG may not be prerequisite for precise measurements of PV. The expected acute increase in PV after infusion of commonly used plasma expanders after cardiac surgery was not found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Menth-Meier et al (28) demonstrated that it is appropriate to perform peripheral dye injection for PV measurement by ICG-DT. However, others advised induction of hyperemia before dye injection to accelerate recirculation (14,28).…”
Section: Determining Icg Concentrationmentioning
confidence: 99%
See 3 more Smart Citations
“…Menth-Meier et al (28) demonstrated that it is appropriate to perform peripheral dye injection for PV measurement by ICG-DT. However, others advised induction of hyperemia before dye injection to accelerate recirculation (14,28).…”
Section: Determining Icg Concentrationmentioning
confidence: 99%
“…Menth-Meier et al (28) demonstrated that it is appropriate to perform peripheral dye injection for PV measurement by ICG-DT. However, others advised induction of hyperemia before dye injection to accelerate recirculation (14,28). Additionally, in preliminary, unpublished experiments (n ϭ 10), we established that injection into one peripheral catheter and withdrawal of the timed samples from this and, simultaneously, an additional catheter on the other arm led to the same PV:…”
Section: Determining Icg Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indocyanine green (ICG), besides monitoring hepatosplanchnic blood flow (Sakka et al 2007, Stehr et al 2005, has been frequently used for PV measurements (Belin de Chantemèle et al 2006, Bradley and Barr 1968, Haller et al 1992, Jacob et al 2003, Rehm et al 1998, 2000a, 2000b). Although PV is intra-individually inconstant, validation of this method has been performed successfully (Haneda and Horiuchi 1986, Jacob et al 2007, Menth-Meier et al 2001. Repeatability of the ICG-dilution technique (ICG-DT) has been shown to be excellent (Haller et al 1993, Rehm et al 1998 as has the accuracy (Menth-Meier et al 2001), provided circulatory steady-state conditions are maintained between two corresponding measurements (Jacob et al 2007).…”
Section: Introductionmentioning
confidence: 99%